Spectrum of Pathogenic Variants of the ATP7B Gene and Genotype–Phenotype Correlation in Eastern Eurasian Patient Cohorts with Wilson’s Disease - Mikhail Garbuz; Elena Ovchinnikova; Anna Ovchinnikova; Valeriya Vinokurova; Yulya Aristarkhova; Olga Kuziakova; Mariya Mashurova; Vadim Kumeiko (Biomedicines)
Background/Objectives: Wilson’s disease (WD) (OMIM 277900) or hepatolenticular degeneration is an autosomal recessive disorder caused by impaired copper excretion with subsequent accumulation in the liver, brain, and other tissues of the body. The defects in copper metabolism are based on various pathogenic variants of the ATP7B gene encoding copper-transporting P-type ATPase. The aim of this work is to search for pathogenic variants of the ATP7B gene among Eastern Eurasian patient cohorts and to pick correlations between pathogenic variants, gender, age of onset of the disease, and the course of the disease. Methods: The material for the study was the biomaterial of 100 people. The search for mutations was carried out by Sanger sequencing. Multiple alignment of nucleotide sequences and their analysis was performed using the MEGA-X software. To study the genotype-phenotypic correlation, an analysis of the medical records of each patient was carried out. Results: Most common pathogenic variant (48%) in the sample is p.His1069Gln (c.3207C>A), located in exon 14 of the ATP7B gene. Pathogenic variants of p.Glu1064Lys (c.3190G>A)—20%—and p.Met769HisfsTer26 (c.2304insC)—8%—of exons 14 and 8 were also common. For patients with pathogenic alleles p.His1069Gln (c.3207C>A) and p.Glu1064Lys (c.3190G>A), typical deviations are mental and neurological manifestations of WD. In patients with the pathogenic allele p.Met769HisfsTer26 (c.2304insC), deviations are more characteristic of the liver and a combination of various symptoms that are atypical for WD. Conclusions: In this study, we were able to obtain differences in symptoms in patients with different pathogenic alleles of the ATP7B gene.